Signal Transduction and Smooth Muscle - Trebak, Mohamed; Earley, Scott (Methods in Signal Transduction Series, 2019)
All hollow organs, such as blood vessels, the gastrointestinal tract, airways, male and female reproductive systems, and the urinary bladder are primarily composed of smooth muscle. Such organs regulate flow, propulsion and mixing of luminal contents and storage by the contraction and relaxation of smooth muscle cells. Smooth muscle cells respond to numerous inputs, including pressure, shear stress, intrinsic and extrinsic innervation, hormones and other circulating molecules, as well as autocrine and paracrine factors. This book is a review of smooth muscle cell regulation in the cardiovascular, reproductive, GI, and other organ systems with emphasis on calcium and receptor signaling.